Analysis of Non-coherent Receivers for Suppression of NBI in UWB Communication System (International Journal of Engineering and Computer Science, 2015)
A new promising technique adopted by 4G community is Ultra-Wide Band (UWB) technology, which offers a solution for high bandwidth, high data rate, low cost, low power consumption, position location capability. One type of UWB communication is impulse radio. The paper discusses the effectiveness of major UWB schemes using non coherent receivers i.e AR receivers: the Transmitted Reference (TR) scheme, Averaged Transmitted Reference (ATR) and Differential Transmitted Reference (DTR) scheme. Performance comparison using Matlab Simulation reveals that ATR and DTR receiver outperforms the conventional TR receiver by 3 − 4 dB  in  IEEE 802.15.4a environment.